2015
DOI: 10.1109/tns.2015.2470665
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Modeling of Radiation-Induced Defect Dynamics in Electronic Devices

Abstract: Density functional theory (DFT) has emerged as a powerful tool to model defect properties and dynamics at the quantum mechanical level. Results from targeted DFT calculations can provide valuable insight into the atomistic nature of radiation-induced defect phenomena in microelectronics. This review describes the foundations of DFT, its implementations, and defect calculations. Illustrative examples from recent studies are presented in which DFT calculations, combined with experiments, have led to new insights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 102 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…A mechanism is the dissociation of H 2 molecules at the positively charged oxygen deficiency defects, [14,15] such as E δ and E γ centers, which has been investigated by first-principles calculations. [16][17][18] It has been shown that H 2 molecules react with these positively charged defects, producing protons and neutral hydrogenated defects. This mechanism tends to be dominant if there is a sufficient supply of H 2 molecules, which can be the residue of hydrogen exposed in processing.…”
Section: Introductionmentioning
confidence: 99%
“…A mechanism is the dissociation of H 2 molecules at the positively charged oxygen deficiency defects, [14,15] such as E δ and E γ centers, which has been investigated by first-principles calculations. [16][17][18] It has been shown that H 2 molecules react with these positively charged defects, producing protons and neutral hydrogenated defects. This mechanism tends to be dominant if there is a sufficient supply of H 2 molecules, which can be the residue of hydrogen exposed in processing.…”
Section: Introductionmentioning
confidence: 99%